Universal Method for Producing Reduced Graphene Oxide/Gold Nanoparticles Composites with Controlled Density of Grafting and Long-Term Stability - Piotr Szustakiewicz (Nanomaterials, 2019)
In this study, we report a universal approach allowing the non-covalent deposition of gold nanoparticles on reduced graphene oxide surface in a controlled fashion. We used a modified Hummers method to obtain graphene oxide, which then underwent surficial functionalization with carboxyl moieties coupled with simultaneous reduction. Nanoparticles were synthesized ex-situ and capped with a thiolated poly-ethylene glycol (PEG) ligand. The interactions between the surface of modified graphene oxide and nanoparticle ligands enabled the formation of stable hybrid graphene-nanoparticles materials in the aqueous phase. Using this technique, we were able to cover the surface of graphene with gold nanoparticles of different shapes (spheres, rods, triangles, stars, and bipyramids), broad range of sizes (from 5 nm to 100 nm) and controlled grafting densities. Moreover, materials obtained with this strategy exhibited long-term stability, which coupled with the versatility and facility of preparation, makes our technique appealing in the light of increasing demand for new graphene-based hybrid nanostructures.